1985
DOI: 10.1159/000176990
|View full text |Cite
|
Sign up to set email alerts
|

Copper Deficiency Effects on Cardiovascular System and Lipid Metabolism in the Rat; the Role of Dietary Proteins and Excessive Zinc

Abstract: Weanling rats were fed a copper-deficient purified diet. The effects of varying the type of protein and supplements of copper and zinc on cardiovascular pathology and some biochemical parameters were investigated. It was found that cardiomyopathy developed in the copper-deficient groups. Milk powder caused significant exacerbation of this development relative to dietary casein or egg white. Angiopathy developed only when dietary zinc was 20 ppm. Dietary copper did not change this situation. Serum cholesterol w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…Copper deficiency has long been known to alter lipid metabolism; consequently, it has been proposed as a significant factor in human diseases associated with dyslipidemia (15). Copper deficiency is rarely diagnosed in humans, with a notable exception of a growing number of reports pointing to copper and other mineral insufficiencies as unintended consequences of bariatric surgeries (16)(17)(18).…”
Section: Copper In Western Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper deficiency has long been known to alter lipid metabolism; consequently, it has been proposed as a significant factor in human diseases associated with dyslipidemia (15). Copper deficiency is rarely diagnosed in humans, with a notable exception of a growing number of reports pointing to copper and other mineral insufficiencies as unintended consequences of bariatric surgeries (16)(17)(18).…”
Section: Copper In Western Dietmentioning
confidence: 99%
“…Although numerous studies clearly link copper deficiency to altered lipid metabolism in animal models (12,22,24,(89)(90)(91)(92) and human volunteers (29), only recently has low dietary copper been implicated in liver dyslipidemia pathology, including non-alcoholic fatty-liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH). In a recent groundbreaking study, hepatic copper content in biopsy specimens was inversely correlated with the severity of fatty liver disease, and copper deficiency in a rodent model was found sufficient to induce NAFLD and metabolic syndrome (12).…”
Section: Copper and Nafldmentioning
confidence: 99%
“…It has been recently reported that growing male rats fed a copper-deficient diet for 90 days develop cardiomyopathy by dilatation, depending solely on the degree of deficiency determined by standard nutritional criteria [3,4]. This condition was found to be exac erbated when sucrose instead of starch was the sole source of carbohydrate in the diet or when defatted whole milk powder rather than egg white or casein was the sole source of dietary protein.…”
Section: Introductionmentioning
confidence: 99%
“…In analyzing the data previously reported [3,4] for possible biochemical mechanisms for the development of the myocardial pa thology accompanying the feeding of copperdeficient diets to rats, it was recognized that a possible factor may have been the coinci dental functional iron deficiency resulting from feeding the copper-deficient diet [5,6], This, as is well known, is due to the inability of copper-deficient rats and other mammals to utilize liver iron stores for hematopoiesis and other processes. A search of the litera ture on the nutrition and metabolism of iron failed to find any reference to the develop ment of cardiomyopathy as a result of exper imental or clinical iron deficiency [7], In general, attention to the effects of iron defi ciency on the myocardium was notably ab sent in reviews on the subjects [8][9][10], There fore, an experiment was designed to examine solely the effect of iron deficiency (Fe-) on the developing myocardium of growing rats.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because these enzymes are found within most tissues, the effects of copper deficiency are systemic and widespread 9 • Copper is essential for the development of healthy bones 10, skin 11, and blood vessels 12. The cardiovascular system is especially sensitive to copper levels 13. The strongest evidence for this can be found by the extreme consequences of copper deficiency mainly manifesting as damage to the heart and blood vessels l4 .…”
Section: Introductionmentioning
confidence: 99%